2017
DOI: 10.1371/journal.pone.0187165
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and impact of pain in women treated with aromatase inhibitors for breast cancer. A multicenter cohort study

Abstract: Women with hormone-dependent breast cancer are treated with aromatase inhibitors (AI) to slow disease progression by decreasing estrogen levels. However, AI have adverse effects, including pain, with potentially serious impact on quality of life (QOL) and treatment compliance. We evaluated quality of life during the first year of AI treatment, focusing particularly on the impact of pain. In a multicenter cohort study of 135 women with early-stage breast cancer, free of pain at the initiation of AI treatment, q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Our results highlight the diversity of experiences of side effects as many patients reported different side effects from one day to the next, with substantial variance in how distressful the event was perceived. Previous studies have reported hot flashes, night sweats, fatigue, mood swings and weight loss/gain (Moon et al, ), as well as musculoskeletal symptoms and sleeping disorders (Laroche et al, ). However, a strength of this study was that data were collected for a longer period of time than in previous studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results highlight the diversity of experiences of side effects as many patients reported different side effects from one day to the next, with substantial variance in how distressful the event was perceived. Previous studies have reported hot flashes, night sweats, fatigue, mood swings and weight loss/gain (Moon et al, ), as well as musculoskeletal symptoms and sleeping disorders (Laroche et al, ). However, a strength of this study was that data were collected for a longer period of time than in previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…For women diagnosed with hormone‐receptor‐positive breast cancer, endocrine therapy (ET), that is tamoxifen (TAM) or aromatase inhibitors (AI) is recommended for at least five years, to reduce recurrence and rates of mortality (Davies, Godwin, & Gray, ). Patients may experience diverse side effects related to their specific treatment (Laroche, Perrot, & Medkour, ; Moon, Hunter, Moss‐Morris, & Hughes, ), and difficulties in managing these side effects have been identified as obstacles for treatment adherence (Bluethmann et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found beneficial effects of vitamin D supplementation on musculoskeletal pain in BC patients receiving aromatase inhibitor therapy [22,45,46]. Among adverse effects of aromatase inhibitors, pain has a negative impact on quality of life, on treatment compliance and on survival of BC patients [47][48][49][50]. A possible mechanism for the beneficial effect of vitamin D arthralgia and myalgia may be its anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the impact of breast cancer treatment on the QoL of patients is not only important for patients and their health care providers but also critical for policymakers to evaluate the cost‐effectiveness of cancer treatments. Most previous studies focused on the QoL associated with a specific breast cancer treatment of interest (i.e., tamoxifen only; Boehm et al, ; Kilickap et al, ; van Nes et al, , AIs only; Kilickap et al, ; Laroche et al, ; van Nes et al, , chemotherapy only; Bayram et al, ; Browall et al, ; Galalae et al, ; Ganz et al, ; Hwang et al, ; Tiezzi et al, , radiotherapy only; Rahn et al, ; Xiao et al, , mastectomy only; Kaminska et al, ; Szutowicz‐Wydra et al, ), whereas this study comprehensively evaluated the QoL across different cancer treatments. We found that the use of chemotherapy had the most significant association with the QoL of breast cancer survivors, with adjustment for patient's characteristics and other breast cancer treatments; no significant association was not found for other types of breast cancer treatment.…”
Section: Discussionmentioning
confidence: 99%